(2x-1)*(4x^2+2x+1)-4x*(2x^2-3)+23

Question

(2x-1)*(4x^2+2x+1)-4x*(2x^2-3)+23

in progress 0
Khang Minh 1 year 2020-10-14T06:06:08+00:00 2 Answers 103 views 0

Answers ( )

    0
    2020-10-14T06:07:09+00:00

    ( 2x – 1 )( 4x² + 2x + 1 ) – 4x( 2x² – 3 ) + 23

    = ( 2x )³ – 1³ – 8x³ + 12x + 23

    = 8x³ – 1 – 8x³ + 12x + 23

    = 12x + 22

    0
    2020-10-14T06:07:28+00:00

    Đáp án:

    $12x+22$

    Giải thích các bước giải:

    $(2x-1).(4x^2+2x+1)-4x.(2x^2-3)+23$

    $⇔8x^3+4x^2+2x-4x^2-2x-1-8x^3+12x+23$

    $⇔12x+22$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )